Vitamin D Deficiency in Critically Ill Children in Karachi - Falak Abro, Fozia Baloch, Mehtab Hussain, Asma Noreen, Nadeem Noor, Uzma Arshad, Bushra Rafique (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To evaluate vitamin D levels in critically ill children. Subject and methods: There were 114 critical ill patients, who were admitted in pediatric ICU with severe respiratory depression (sat < 90%), infection (WBC > 10X 103), myocarditis (EF < 40%). Blood sample was drawn for evaluation of vitamin D levels. Results:- The average age of the children was 4.95±2.7 years. There were 63(55.26%) male and 51(44.74%) female. Frequency of vitamin D deficiency in critically ill patients was observed in 55.26% (63/114) children. Conclusion: - In our study, critically ill children had higher frequency of vitamin D deficiency.